Rancangan Arsitektur Sistem Informasi E-Customer Relationship Management Menggunakan Metode Enterprise Unified Process - Retno Wulandari; Kristoko Dwi Hartomo (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Customer Relationship Management (CRM) is a management that discusses the handling of the relationship between customers and the company. In the Power Kitchen where one of the company's equipment in the city of Surabaya has problems related to handling complaints from customers. So we need a CRM system to build relationships with customers. Therefore, the Power Kitchen company needs a CRM system to make it easier for companies to handle complaints from customers. This research uses the Enterprise Unified Process method which is a framework for the software process used. This research has resulted in the form of recommendations for system architecture models to achieve company goals and service relationships between companies and customers.